2003
DOI: 10.1080/02757540310001609370
|View full text |Cite
|
Sign up to set email alerts
|

Changes in nutrient content and stable isotope ratios of C and N during decomposition of seagrasses and mangrove leaves along a nutrient availability gradient in Florida Bay, USA

Abstract: The decomposition of the mangrove Rhizophora mangle and the seagrass Thalassia testudinum was examined using litterbags along a natural gradient in nutrient availability. Seagrass leaves had a higher fraction of their biomass in the labile pool (57%), compared to mangrove leaves (36%) and seagrass rhizomes (29%); the overall decomposition rates of the starting material reflected the fractionation into labile and refractory components. There was no relationship between the N or P content of the starting materia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
93
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 111 publications
(102 citation statements)
references
References 33 publications
8
93
1
Order By: Relevance
“…Our estimated C org stocks for the study sites were generally lower (627-4324 t C km −2 ) than estimates (25 200-84 000 t C km −2 ) found in the literature (Nelleman et al, 2009;Fourqurean et al, 2012). Several of the studies were conducted in the Mediterranean P. oceanica meadows -a habitat with superior carbon sequestration and storage capacity (Duarte et al, 2005;Lavery et al, 2013).…”
Section: Geographical Comparisons Of Carbon Stocks and Accumulationcontrasting
confidence: 54%
See 4 more Smart Citations
“…Our estimated C org stocks for the study sites were generally lower (627-4324 t C km −2 ) than estimates (25 200-84 000 t C km −2 ) found in the literature (Nelleman et al, 2009;Fourqurean et al, 2012). Several of the studies were conducted in the Mediterranean P. oceanica meadows -a habitat with superior carbon sequestration and storage capacity (Duarte et al, 2005;Lavery et al, 2013).…”
Section: Geographical Comparisons Of Carbon Stocks and Accumulationcontrasting
confidence: 54%
“…Recent studies have shown considerable variation in the global estimates of carbon stocks (C org stocks) and carbon accumulation rates (C org accumulation) in seagrass meadows, indicating an incomplete understanding of factors influencing this variability (Fourqurean et al, 2012;Duarte et al, 2013a;Lavery et al, 2013;Miyayima et al, 2015). The Baltic Sea forms a key distribution area for eelgrass in Europe, but similarly to the global data sets, we have so far lacked estimates on seagrass carbon stocks and accumulation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations